2017
DOI: 10.18203/2320-6012.ijrms20171865
|View full text |Cite
|
Sign up to set email alerts
|

Medical thoracoscopy- an experience

Abstract: Background: Medical thoracoscopy is a minimally invasive procedure for diagnosing and treating pleural diseases especially undiagnosed exudative pleural effusion. It is cost effective and safe. The diagnostic yield in undiagnosed pleural effusion is excellent.Methods: This prospective observational study was done in Government Chest Disease hospital of Government Medical College, Srinagar during the period between December 2015 to Dec 2016.Thirty undiagnosed pleural effusion patients after thoracocentesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(22 reference statements)
3
2
0
Order By: Relevance
“…We also found plural thickening in a few. These findings were in concordance with Helala et al, 21 Shah et al, 14 and Prabhu and Narasimhan 22 studies. On correlation of physical finding with clinical diagnosis we found that the most common diagnosis with sago grain appearance of pleura was TB as in Helala et al, 21 Shah et al, 14 and Mishra et al 20 This was found to be statistically significant(P=0.012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also found plural thickening in a few. These findings were in concordance with Helala et al, 21 Shah et al, 14 and Prabhu and Narasimhan 22 studies. On correlation of physical finding with clinical diagnosis we found that the most common diagnosis with sago grain appearance of pleura was TB as in Helala et al, 21 Shah et al, 14 and Mishra et al 20 This was found to be statistically significant(P=0.012).…”
Section: Discussionsupporting
confidence: 92%
“…These findings were in concordance with Helala et al, 21 Shah et al, 14 and Prabhu and Narasimhan 22 studies. On correlation of physical finding with clinical diagnosis we found that the most common diagnosis with sago grain appearance of pleura was TB as in Helala et al, 21 Shah et al, 14 and Mishra et al 20 This was found to be statistically significant(P=0.012). Whereas most common diagnostic finding of nodular appearance of pleura was malignancy which was in concordance with studies conducted by Helala et al, 21 Prabhu and Narasimhan, 22 and Mishra et al 20 This association was not found to be statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Various studies across the globe have reported similar diagnostic yield (4,(11)(12)(13)(14)(15)(16). Studies from Indian subcontinent reported diagnostic yield ranging from 66% to 97% (17)(18)(19)(20)(21)(22). Some of the studies included non-specific pleuritis as a final diagnosis that has increased their diagnostic yield (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%